2013
DOI: 10.3109/2000656x.2012.755928
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of preserving or splitting the carpal ligament in carpal tunnel operation

Abstract: Carpal tunnel syndrome is treated very successfully by surgical release of the flexor retinaculum. However, in some patients, all symptoms are not resolved. Weakness in grip strength and pain in the thenar and hypothenar areas corresponding to the end of the transverse ligament after its complete section have been described as common complications of classical neurolysis of the median nerve. This study presents here the long-term results of decompression operation of the median nerve at the wrist, conserving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A similar prospective study compared endoscopic carpal tunnel decompression with open carpal tunnel decompression and did not find differences between the two techniques in functional and electromyography outcomes, despite a significant shortening in median nerve motor distal latency and an increase in the velocity of sensory conductions in both groups [34]. A retrospective analysis of 114 CTS patients compared two surgical procedures, namely, classical open neurolysis of the median nerve with flexor retinaculum lengthening according to the Simonetta technique, and demonstrated that ligamentoplasty according to the Simonetta technique led to better manual force in 10 years of follow-up [35]. A prospective, randomized, double-blind, controlled trial involving 50 CTS patients compared the longitudinal epineurotomy of the median nerve with the simple dissection of the carpal ligament and found no differences in distal motor latency, distal sensory latency, or grip strength after 180 days of follow-up [36].…”
Section: Discussionmentioning
confidence: 99%
“…A similar prospective study compared endoscopic carpal tunnel decompression with open carpal tunnel decompression and did not find differences between the two techniques in functional and electromyography outcomes, despite a significant shortening in median nerve motor distal latency and an increase in the velocity of sensory conductions in both groups [34]. A retrospective analysis of 114 CTS patients compared two surgical procedures, namely, classical open neurolysis of the median nerve with flexor retinaculum lengthening according to the Simonetta technique, and demonstrated that ligamentoplasty according to the Simonetta technique led to better manual force in 10 years of follow-up [35]. A prospective, randomized, double-blind, controlled trial involving 50 CTS patients compared the longitudinal epineurotomy of the median nerve with the simple dissection of the carpal ligament and found no differences in distal motor latency, distal sensory latency, or grip strength after 180 days of follow-up [36].…”
Section: Discussionmentioning
confidence: 99%